Ginsenoside Rg3 Attenuates Lipopolysaccharide-Induced Acute Lung Injury via MerTK-Dependent Activation of the PI3K/AKT/mTOR Pathway - Yang, Jing; Li, Senyang; Wang, Luyao; Du, Fen; Zhou, Xiaoliu; Song, Qiqi; Zhao, Junlong; Fang, Rui (Frontiers in Pharmacology, 2018)
Acute lung injury (ALI) is a common clinical disease with high morbidity in both humans and animals. Ginsenoside Rg3, a kind of traditional Chinese medicine extracted from ginseng, and is widely used to cure many inflammation-related diseases. However, the specific molecular mechanism of the effects of ginsenoside Rg3 on inflammation is rarely reported. Thus, we established a mouse model of lipopolysaccharide (LPS)-induced ALI to investigate the immune protective effects of ginsenoside Rg3 and explore the molecular mechanism. In WT mice, we found that ginsenoside Rg3 treatment significantly mitigated pathological damages and reduced myeloperoxidase (MPO) activity and the production of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6); furthermore, the production of anti-inflammatory mediators (IL-10 and TGF-β), polarization of M2 macrophages and expression levels of phosphorylation of PI3K, AKT, mTOR and MerTK were promoted. However, there is no significantly different about the pathological damages, MPO activity, inflammatory cytokines levels, and the protein expression levels of phosphorylation of PI3K, AKT and mTOR in whether LPS treatment group or ginsenoside Rg3 groups in MerTK-/- mice. Taken together, the present study demonstrated that ginsenoside Rg3 could attenuate LPS-induced ALI by decreasing the levels of pro-inflammatory mediators and increasing the production of anti-inflammatory cytokines. And these processes were mediated through MerTK-dependent activation of PI3K/AKT/mTOR pathway. These findings provide a new sight of specific anti-inflammatory mechanism of ginsenoside Rg3.